Teachers in Initial Training Facing the Sustainable Development Goals: A Comparative Study Before and After the COVID-19 Pandemic - Ramón Méndez; María del Mar Felices-de la Fuente (Social Sciences)
Achieving the Sustainable Development Goals (SDGs) is one of the main challenges facing humanity. However, the fulfillment of these goals has been hampered by health and climate crises, as well as international conflicts. Despite this, it remains essential that work is carried out on these UN proposals in all areas, especially in education. This study aims to understand future teachers’ conceptions of the SDGs and the importance they give to teaching them. To do this, a non-experimental quantitative survey-type design was used to compare the results from two academic years (pre-pandemic and post-pandemic) in order to detect any differences. The information was collected via a questionnaire, which was completed by 364 students from the Degree in Primary Education course. The results show an increase in knowledge about the SDGs and a change in the assessment scale regarding the importance of each of its 17 goals. Likewise, there has been an increase in the students’ personal involvement in achieving them, linked to a more pessimistic position about their fulfillment. We conclude that there is a difference in the results between the two contexts, and that teaching about SDGs during teacher training should be reinforced.